THU0553 Low alkaline phosphatase levels: could it be hypophosphatasia?. (15th June 2017) - Tornero, C; Aguado, P; García, S; Tenorio, J; Lapunzina, P; Buño, A; Iturzaeta, JM; Plasencia, C; Monjo, I; Balsa, A
Abstract : Background: Hypophosphatasia (HPP) is a rare inherited disorder of bone and mineral metabolism, caused by mutations in the ALPL (alkaline phosphatase liver type) gene, with reduction of activity of the tissue-non-specific isoenzyme of ALP (TNSALP). The clinical presentation is variable and adult forms of the disease are usually milder than those affecting infants and children, easily overlooked or misdiagnosed, which can lead to erroneous therapeutic decisions. Objectives: The primary objectives of our study are to estimate the prevalence of patients with adult forms of HPP in a group of patients with persistent hypophosphatasemia, to analyze their clinical and functional characteristics and to compare these findings between those presenting or not these mutations. Methods: In this Cross-sectional study, 1.536.711 ALP measurements owing to 386.356 patients were evaluated during a six-year period (2009–2015). Patients having at least two values below 35 IU/l and none above 45 IU/l constituted the study population. In total, 427 patients were included. Among them, 31 patients were excluded because of presenting causes of secondary HPP and 13 because of lost to follow-up. 108 patients were contacted by phone to fulfill a questionnaire about manifestations related to HPP and health assesment and in order to obtain blood samples to perform the genetic test. Results: Demographic and clinical characteristics of both groups are shown in Table 1 . Of the 108 patients evaluated, the genetic test results of 39 patients are available at this moment (the rest of the results are currently pending). 59% (23/39) tested positive for the genetic mutation.Despite data are still partial and although the results did not achieve statistical significance, we observed with a greater relevance a higher proportion of patients with HPP presenting with chronic bone pain (48, 7% vs 25, 6%, p=0, 157), muscle weakness (15, 4% vs 2, 6%, p=0, 112) and more necessity of analgesic medication (p=0, 107) in patients with HPP in comparison with the control group. Furthermore, there was a non-significant trend in the HPP-group to present dental abnormalities and premature dental loss (7, 6%), absent manifestations in the control group (p=0, 123). In addition, orthopedic surgery was more common in the HPP group (12, 8%) compared with the other group (0%), p=0, 04. The prevalence of stress fractures was also higher in patients with HPP (7, 69%). No significant differences were found in demographic characteristics, vertebral fractures, calcific periarthritis, condrocalcinosis, or FRAX index. In terms of biochemical tests, serum phosphate levels were higher in the HPP group (4, 18 mg/dl) in relation to the control group (3, 52 mg/dl), p=0, 05. No differences were observed neither in pain assessment, measured with the Visual Analogue Scale nor in the Health Assessment Questionaire for disability between both groups. Conclusions: The diagnosis of HPP can be difficult and is often missed or delayed, particularly in adults. The prevalence of HPP between patients with persistent low ALP is high and although the clinical presentation is milder in adults, it often presents with chronic bone pain, weakness, stress fractures and dental abnormalities. These data should promote a more proactive attitude towards detection of adult HPP. Disclosure of Interest: None declared